Saia da caverna! de Platão a Paulo Freire, um convite a reflexão filosófica acerca da relação entre ignorância, conhecimento e liberdade. - Andrade, José Roberto Silva (2022)
The following work philosophically addresses the themes of education, freedom and the evils of ignorance. Using education for freedom as a reference from the theory of the philosopher and pedagogue Paulo Freire, our proposal here will be presented as a philosophy for the oppressed. A relationship with the practice of Socratic dialectics will be drawn, which makes us seek philosophical references in maieutics as an educational method, based on the work of Plato. Therefore, in the following chapters, the relationship between freedom, knowledge and ignorance will be analyzed from the perspective of Platonic and Freirean concepts. The relationship between ignorance, deprivation of liberty and education allows us to find nuances in the educational reality in different historical periods in Brazil, giving support to the Freirean proposal as timeless. In this vein, the relevance of this research is based on the demonstration of the legitimacy of the Freirean method of education in the Socratic/Platonic philosophical proposal. That said, the idea of ​​an education for freedom presents itself as an overcoming not only of the ignorance that socially excludes, but also of the fallacy of individual freedom that overlaps with collective interests. In this sense, we will bring to light the political philosophy of Jean Jacques Rousseau, which brings us the thesis that the only possible freedom is that guaranteed by law. Where there is no law, there is no freedom. Thus, his academic reflection aims to question this legitimation of individual freedoms that overlaps with collective interests. No, there is no freedom when it is presented as a right to oppress others, whether in Plato or Paulo Freire, oppressing the other is not freedom, it is actually ignorance. From this point of view, it is imperative to highlight that this text tries in an embryonic way to discuss and reflect on such issues, where we hope to highlight ignorance as a disease. The proposed idea is to highlight that knowledge represents true freedom, so that it becomes the main focus of human existence in all contexts and social classes.